2014
DOI: 10.1007/s00167-014-3286-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between quantitative MRI and ICRS arthroscopic grading of articular cartilage

Abstract: 21Purpose. To investigate the association of quantitative MRI (qMRI) parameters with 22 arthroscopic grading of cartilage degeneration. Arthroscopy of the knee is considered to be the 23 gold standard of OA diagnostics, however, it is operator-dependent and limited to the evaluation 24 of the articular surface. qMRI provides information on the quality of articular cartilage and its 25 changes even at early stages of a disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 49 publications
2
35
1
Order By: Relevance
“…The possibility of diagnosing early cartilage changes with high accuracy could not be proven by our used sequences. These results are confirmed by Casula et al [118], reporting that the loss of cartilage and the quality of remaining tissue in the lesion site is not directly associated with each other, because quantitative MRI parameters (especially T1 relaxation time, T2 relaxation time, and delayed gadolinium-enhanced MRI) were not linearly related to arthroscopic grading in OA.…”
Section: Discussionsupporting
confidence: 74%
“…The possibility of diagnosing early cartilage changes with high accuracy could not be proven by our used sequences. These results are confirmed by Casula et al [118], reporting that the loss of cartilage and the quality of remaining tissue in the lesion site is not directly associated with each other, because quantitative MRI parameters (especially T1 relaxation time, T2 relaxation time, and delayed gadolinium-enhanced MRI) were not linearly related to arthroscopic grading in OA.…”
Section: Discussionsupporting
confidence: 74%
“…Surprisingly, while the medial compartment was the one with the highest prevalence of lesions, differences in quantitative parameters associated with cartilage defects were significant mostly in the lateral compartment. This result confirms that the link between morphological and biochemical changes may not always be obvious in articular cartilage, particularly in early OA . Among the three parameters, only Ad T 2ρ showed a significant difference in the medial compartment.…”
Section: Discussionsupporting
confidence: 77%
“…At the same time, however, decreased T2 in the periphery suggests that there may be other areas in the joint cartilage where up‐regulation and increased synthesis of extracellular matrix proteins occur . This contention is supported by a recent study by Casula et al , who reported that in middle‐aged patients with an arthroscopic International Cartilage Repair Society (ICRS) grade of 0–3, patients with early cartilage pathology (ICRS 1) demonstrated shorter T2 values than patients with arthroscopically normal cartilage (ICRS 0).…”
Section: Discussionmentioning
confidence: 83%